An integrated product-process-organisation model to manage design systems. (4th March 2010) - Robin, Vincent; Girard, Philippe
Today, as many stakeholders take part in the development of a product, project design management has to encourage and favour collaboration among all the actors involved in the project. The indicators on the product are not enough to estimate and increase the performance of the design process. In design, the notion of performance concerns the product, process and organisation. It has to be quantitative and qualitative: quantitative to measure the tangible results on the product and qualitative to estimate the performance of the collaborative design process. In this paper, we are particularly interested in the identification and follow-up of the factors influencing the performance of the design process. We define the elements of the design performance and provide an integrated product-process-organisation model developed to manage the design process. Finally, the Unified Modelling Language (UML) models of a software prototype to help decision makers and an example of a Graphic User Interface (GUI) are also presented.